Survival Skills of the North American Indians. - Goodchild, Peter, 1949- (Chicago Review Press, 1999)
This comprehensive review of Native American life skills covers collecting and preparing plant foods and medicines; hunting animals; creating and transporting fire; and crafting tools, shelter, clothing, utensils, and other devices. Step-by-step instructions and 145 detailed diagrams enable the reader to duplicate native methods using materials available in local habitats. A new foreword, introduction, and index complement the practical information offered.